TV 및 디지털 영상광고에서 나타난 기업광고 특성 분석 - 2020년부터 2021년 기업광고를 중심으로 - 엄남현(Namhyun Um) (한국콘텐츠학회 논문지, 22(8), 2022)
For this study, a total of 297 TV advertisements and digital video advertisements were selected as analysis targets among domestic corporate advertisements executed for two years from 2020 to 2021. As a result of the content analysis, it was found that CSR public service advertisements, CSV advertisements, and ESG advertisements in 2020, when the corona pandemic began in earnest and ESG of companies emerged as a business management topic, showed a markedly higher execution frequency than in 2021. As a result of examining the distribution of corporate advertisement types by media, it was found that companies were executing various corporate advertisements through digital media rather than traditional media such as TV. As a result of examining the advertising appeal strategies according to the types of corporate advertisements, it was found that the emotional appeal strategy was most frequently used among the rational appeal, emotional appeal, and mixed appeal as a whole in corporate advertising. As a result of analyzing the advertisement model types according to the classification of corporate advertisements, it was found that corporate advertisements use a general model differently from brand advertisements. Lastly, as a result of examining the distribution of advertisement model types according to media types, it was found that the celebrity model is more frequently used in TV advertisements for digital advertisements. 본 연구를 위해 2020년부터 2021년까지 2년간 집행된 국내 기업광고 중에서 공중파 TV광고 및 디지털 영상광고를 총 297편을 분석대상으로 선정했다. 내용 분석결과, 코로나 팬데믹이 본격적으로 시작되고, 기업들의 ESG가 기업의 경영 화두로 떠오른 2020년 CSR 공익성 광고와 CSV 광고 그리고 ESG 광고가 2021년에 비해 현격한 집행 빈도가 높은 것으로 나타났다. 매체별 기업광고 종류 분포를 살펴 본 결과, 기업들은 TV라는 전통매체 보다는 디지털 매체를 통한 다양한 기업광고를 집행하고 있다는 것이 밝혀졌다. 기업광고 종류에 따른 광고 소구전략을 살펴 본 결과, 이성적 소구, 감성적 소구, 그리고 혼합소구 중에서 기업광고 전체적으로 감성적 소구 전략이 가장 빈번히 사용된 것으로 나타났다. 기업광고 구분에 따른 광고모델 유형을 분석한 결과, 기업광고는 브랜드 광고들과는 다르게 일반일 모델을 사용하는 것으로 나타났다. 매체 종류에 따른 광고모델 유형 분포를 살펴본 결과, 유명인 모델은 디지털 광고보가 TV 광고에서 더 자주 사용되고 있는 것으로 밝혀졌다.